The integrals in Gradshteyn and Ryzhik. Part 8: Combinations of powers, exponentials and logarithms. - Moll, Victor H.; Rosenberg, Jason; Straub , Armin; Whitworth, Pat (Scientia, 2025)
We describe some examples of integrals from the table of Gradshteyn and Ryzhik where the integrand is a combination of powers, exponentials and logarithms. The expressions for some of these integrals involve the Stirling numbers of the first kind